Diagnostic utility of peripheral endobronchial ultrasound with electromagnetic navigation bronchoscopy in peripheral lung nodules. Issue 5 (21st June 2013) - Chee, Alex; Stather, David R.; MacEachern, Paul; Martel, Simon; Delage, Antoine; Simon, Mathieu; Dumoulin, Elaine; Tremblay, Alain
Abstract Background and objective This study aimed to investigate the diagnostic utility of peripheral endobronchial ultrasound (pEBUS) followed by as‐needed electromagnetic navigation bronchoscopy (ENB) for sampling peripheral lung nodules. Methods The study was a single‐arm, prospective cohort study of patients with peripheral lung nodules. Peripheral lung lesion localization was initially performed using a pEBUS probe with guide sheath. If localization failed with pEBUS alone, ENB was used to help identify the lesion. Transbronchial biopsy, bronchial brush, transbronchial needle aspiration and bronchial washings were performed. Results Sixty patients were enrolled with average lesion size of 27 mm and mean pleural distance of 20 mm. Lesions were found with pEBUS alone in 75% of cases. The addition of ENB improved lesion localization to 93%. However, diagnostic yield for pEBUS alone and pEBUS with ENB were 43% and 50%, respectively. Factors predicting need for ENB use included smaller lesion size and absence of an air bronchus sign on computed tomography. Conclusions ENB improves localization of lung lesions after unsuccessful pEBUS but is often not sufficient to ensure confirmation of a specific diagnosis. Technical improvements in sampling methods could improve the diagnostic yield.